Perancangan Sistem Informasi Surat Referendum Usulan Kenaikan Pangkat atau Jabatan Berbasis Web - Yudi Prabowo; Ike Pertiwi Windasari; Kodrat Iman Satoto (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2015)
The rapid growth of information and communication technology (ICT) facilitate human activity. Senate of the Faculty of Engineering, University of Diponegoro , as the highest representative body of normative and within the faculty , has one of the tasks that provide feedback on a proposed referendum letter promotion . In the current procedure , the data is stored in the form of the proposed paper form . This method is less efficient , time-consuming addition , members often did not give his opinion because of forgotten or busy with other activities . The purpose of this study is to design a new, computerized information system that is capable of handling data storage process in the Senate , a notice of the proposed promotion, and management approval of the proposed increase in the post. Development of Information System was developed using FAST ( Framework for the Application of System Technique) . This information system development using PHP programming language ased on CodeIgniter framework . Storage and management of databases using a DBMS ( Database Management System MySQL . Testing Information System using User Acceptance testing , that using BlackBox Methodology . The results of this study is to produce a system that can accommodate the proposed promotion, responses senate , and spread in the form of an SMS message to the senate . So that this system can replace the system that is currently running are still less efficient and is manual .